Regulation of alternative 3' splice site selection by constitutive splicing factors. - Lin, C H (1995)
We have devised an in vitro splicing assay in which the mutually exclusive exons 2 and 3 of alpha-tropomyosin act as competing 3' splice sites for joining to exon 1. Splicing in normal HeLa cell nuclear extracts results in almost exclusive joining of exons 1 and 3. Splicing in decreased nuclear extract concentrations and decreased ionic strength results in increased 1-2 splicing. We have used this assay to determine the role of three constitutive pre-mRNA splicing factors on alternative 3' splice site selection. Polypyrimidine tract binding protein (PTB) was found to inhibit the splicing of introns containing a strong binding site for this factor. However, the inhibitory effect of PTB could be partially reversed if pre-mRNAs were preincubated with U2 auxiliary factor (U2AF) prior to splicing in PTB-supplemented extracts. For alpha-tropomyosin, regulation of splicing by PTB and U2AF primarily affected the joining of exons 1-3 with no dramatic increases in 1-2 splicing being detected. Preincubation of pre-mRNAs with SR proteins led to small increases in 1-2 splicing. However, if pre-mRNAs were preincubated with SR proteins followed by splicing in PTB-supplemented extracts, there was a nearly complete reversal of the normal 1-2 to 1-3 splicing ratios. Thus, multiple pairwise, and sometimes antagonizing, interactions between constitutive pre-mRNA splicing factors and the pre-mRNA can regulate 3' splice site selection.